Patient Satisfaction Toward Medical Ward Services In Hospital Universiti Sains Malaysia (HUSM) AND Hospital Kota Bharu (HKB) - Winn, Than; Baba, Abdul Aziz (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2004)
There are several definitions of patient satisfaction given hy different authors. For instance, Steiber defined satisfaction as a subjective perception of the customer who receives a service (Steiber,1990). Pascoe defined patient satisfaction as a health care recipient's reaction to salient aspects of (his or her) service experience. In Pascoe's definition, he assumed that patient satisfaction has a cognitive evaluation and an emotional reaction to the structure, process and outcome of care (Pascoe,1983). Pascoe further defined patient satisfaction into two-parts, firstly; the 'contrast · model which stated that whenever the service experience is greater than the patient's expectations, he or she is satisfied. On the other hand, the 'assimilation' model stated that when the patient does not fully understand the service experience (due to inadequacy of clinical knowledge), he or she may adjust their expectations downward if the sen ice experience falls below expectations. This assimilation model may explain about the higher satisfaction rating of health personnel compared to lower non-clinical experience such as satisfaction rating for hospital food or parking facility (Pascoe, 1983 ). Linder-Pelz defined patient satisfaction as positive evaluations of distinct dimensions of health care bnsed on pnticnt expectations nnd provider performnncc:. Exmnplcs of hcnlth cnrc include the treatment received by patients during their illness episode, a clinic visit, a healthcare setting or the whole health system itself. Patient satisfaction must be understood within a context that contained multiple construct (elements) likely to satisfy the patient (LinderPelz S, 1982b). Importance of Patient Satisfaction Measurement of patient satisfaction can fulfil several functions such as description of health care services from the patient's point of view, a measure of the proc1ess of care and evaluation of health care (Sitzia and Wood,1997). If health manager can identify source of patient dissatisfaction, the health organization can address system weakness and improve their service to patients (Strasser and Davis, 1991 ). Satisfied patients are less likely to disenroll from health plans and more likely to return to a physician or hospital and less likely to bring a malpractice suit (Steiber and Krowinski, 1990). Satisfied patients are more likely to maintain consistent relationship with their healthcare provider (Wartman, 1983 ). Predictors of patient satisfaction Factors as~umed to be related to patient satisfaction include physical and psychological status, attitudes and expectations toward medical care also the structure, process and outcome of care, patient sociodemographic characteristics (Cleary and Mcneil, 1988).Structure of care a. The organization and financing of care The way in Which medical care is organized and financed may be related to patient satisfaction. This means that the provider and organizational characteristics which result in more personal care and better communication with their patient are associated with higher levels of satisfaction (Cleary and McNeil, 1988). Process of care a. Technical Quality of Care Satisfaction with the ambulatory care mostly is associated with satisfaction toward the treating physician while the inpatient experience is more associated with the quality of staff. With the physician, patient satisfaction breaks down into two aspects (i) satisfaction with perceived technical competence and (b) satisfaction with interpersonal skills (Hall and Doman, 1988). On the other hand, nurses, midwives and physician assistants tend to be scored highly on interaction with patients because patients often emphasized on the interpersonal aspect, rather than on perceived technical competence (Hall et al., 1990). b. Interpersonal Aspects of Care People like to have doctors talk to them in an egalitarian way, listen, ask a lot of questions, answer a lot of questions, explain their health condition in a simple way that the patient can understand, and allow patients to make decisions about their care ( Hall et at., 1988). Outcome of care A sntisfnction study townrd three typeg or hospitnl services (tncdicn • nursing nnd supportive) using structured interview method (n=476) found when patients perceived that their health improved, patient satisfaction increased (Carmel, 1985). Sociodemographic characteristics In her meta-analysis on patient satisfaction studies, average magnitudes of relationship between sociodemographics characteristics with patient satisfaction were very small. Older age was the strongest correlate of satisfaction (mean r=O.l3). <:Jreater patient satisfaction was significantly associated with greater age and less (:ducation, and marginally associated with having higher social status and being married. l~o relationship between satisfaction and gender, ethnicity, income or family size (Hall & I>oman, 1990). Literature review Several patient satisfaction studies have been conducted in various diffen~nt setting and medical specialities to address dillerent issues. For instance, n descriptive correlation study in a Emergency department found that 28 patients generally satisfied with the four areas of Emergency department being examined i.e. nursing care, information received, ancillary services, and environment (Bruce et al, 1998). In a client satisfaction study (n=1913). toward health care provided in government health facilities of rural Bangladesh, the important predictors for client satisfaction was healthcare provider interpersonal behaviour (especially respect and politeness) and a reduction in waiting time (on average to 30 min) (Aldana et al., 2001 ). An example of satisfaction studiesfocusing on specialty services was a satisfaction study toward cardiac speciality services in coronary care unit of Ontario hospitals in Canada.